Static and Dynamic Mechanical Properties of Recycled Concrete under Microwave Irradiation - Dandan Shi; Qingxuan Shi; Lei Yang (International Journal of Polymer Science)
The application of recycled concrete can alleviate environmental pollution and has great practical value. In this study, microwave irradiation technology is used to treat recycled concrete in order to obtain reinforced recycled coarse aggregate. Then, the quasi-static and dynamic mechanical properties of concrete (C), recycled concrete (RC), and recycled concrete irradiated by microwave (MRC) were studied, and the effect of the replacement rate of coarse aggregates on its mechanical properties was also studied. The results showed that the quasi-static compressive strength of MCR is higher than that of CR at all replacement rates. With the increase in the replacement rate, the quasi-static compressive strength of MCR decreases gradually, while the quasi-static compressive strength of CR decreases first and then increases, reaching the minimum value at 60%. The dynamic mechanical properties of CR and MCR all have an obvious strain rate effect. The dynamic increase factor (DIF) has an exponential relationship with the natural logarithm of the strain rate. The dynamic constitutive model of RC was established based on composite material mechanics and viscoelastic theory. The research content can provide guidance and basis for the study of mechanical properties and constitutive relationship of RC.